VIR BONUS, COGNOSCENDI PERITUS - Bering, Piotr (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The paper contains a memoir of famous Polish researcher of Medieval Latin Professor Kazimierz Liman (1925–2010) written by his scholar.
Keywords: medieval latin; Poznań University; biography; 20th century